2023
DOI: 10.1161/jaha.122.027635
|View full text |Cite
|
Sign up to set email alerts
|

Cause‐Specific Mortality of Patients With Atrial Septal Defect and Up to 50 Years of Follow‐Up

Abstract: Background This study aimed to evaluate the long‐term mortality and cause‐specific mortality of patients with atrial septal defect (ASD) in a nationwide cohort. Methods and Results All patients diagnosed with simple ASD in the hospital discharge registry from 1969 to 2019 were included in the study. Complex congenital defects were excluded. Each subject was matched with 5 controls according to sex, age, and municipality at the index time. Adjusted morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…2,14 Furthermore, in patients with ASD, undergoing ASD closure has been associated with a lower incidence of AF, stroke, and mortality compared with cases where closure was not performed. 13 Some studies have reported no difference in cardiovascular outcomes among patients with ASD irrespective of intervention. 8,9,15 However, other studies have reported superior outcomes in the intervention group compared with the surgical group in terms of complications including stroke and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,14 Furthermore, in patients with ASD, undergoing ASD closure has been associated with a lower incidence of AF, stroke, and mortality compared with cases where closure was not performed. 13 Some studies have reported no difference in cardiovascular outcomes among patients with ASD irrespective of intervention. 8,9,15 However, other studies have reported superior outcomes in the intervention group compared with the surgical group in terms of complications including stroke and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,9 Even after ASD closure, the prevalence of various cardiovascular complications was higher in individuals with ASD than in the general population. 10,13 However, in cases where symptoms are present or there is progression in right ventricular remodeling or an increase in pulmonary arterial pressure, early ASD closure is recommended. 2,14 Furthermore, in patients with ASD, undergoing ASD closure has been associated with a lower incidence of AF, stroke, and mortality compared with cases where closure was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we found that ASD patients had an increased risk for ischemic heart disease mortality [ 13 ]. In line with that finding, we demonstrated an increased risk of new-onset ischemic heart disease during the follow-up in the current (RR 1.73).…”
Section: Discussionmentioning
confidence: 99%
“…Significant shunts trigger a cascade of pathological alterations in cardiac chambers and pulmonary vasculature, including an increased in the right atrial pressure, right‐sided enlargement, and pulmonary hyperperfusion, which may lead to damage to the right atrial reservoir, pulmonary vascular remodeling, and elevated pulmonary vascular resistance (PVR), ultimately resulting in heart failure and pulmonary arterial hypertension (PAH) in larger and untreated ASD 107,108 . Compared with general community, patients with ASD have a higher overall mortality due to congenital malformations, stroke, heart disease, other diseases of the circulatory, and disease of the endocrine and respiratory systems, even after ASD closure 109 …”
Section: Atrial Septal Defectmentioning
confidence: 99%